Response time of global deltas to changes in fluvial sediment supply - Jie Wang; Zhijun Dai; Xuefei Mei; Huan-Feng Duan; Jaap H. Nienhuis (Nature Communications)
Abstract Fluvial sediment supply supports global delta growth, yet the relationship between these two key variables remains difficult to verify for modern river deltas. Part of the complication might be that deltas are slow to adjust to changes in fluvial sediment supply. To test this hypothesis, here we analyze yearly time series of fluvial sediment supply and delta land area changes for 60 major deltas through 1990–2020. Cross-correlations show that, globally averaged, changes in delta growth rate lag 6 years behind fluctuations in fluvial sediment supply. For the 24 deltas with increased sediment supply, the lag time of land change rates was reduced to 1 year; while the 36 deltas supplied with lower fluvial sediment loads lagged by 6 years. High sediment availability in river-dominated deltas leads to a quicker response of delta land area to upstream supply changes, and deltas with stronger tidal dominance have a subdued response with long lag times. Our findings here highlight the high vulnerability of deltas and their ecosystems to changing external drivers.